The Eschatological Character of Our Knowledge of God - Macdonald, Paul A., Jr. (Modern theology, 2006)
In this essay, I show how Thomas Aquinas circumscribes epistemological questions concerning both the possibility and character of our knowledge of God within a larger eschatological framework that acknowledges the beatific vision as the ultimate good that we desire as well as the ultimate end for which we were created. Thus, knowledge of God is possible and actual on Aquinas's view because it is eternally rather than merely temporally indexed—that is, properly attributable to the blessed in heaven and only derivatively attributable to persons of faith. I further argue that interpreting Aquinas's account of faith in the light of his account of the beatific vision allows us to carve out polemical space for the theologically realist claim that there can be and in fact is objectivity in our knowledge of God, whether that knowledge comes through faith (in this life) or the beatific vision (in the next life).